AUTHENTIC TEXTS FOR CRITICAL READING ACTIVITIES - Ila Amalia (English Department - University of Sultan Ageng Tirtayasa, 2016)
This research takes an action research aimed at promoting critical reading (“thinking” while reading) skills using authentic materials among the students. This research also aims to reveal the students perception on using critical reading skills in reading activities. Nineteen English Education Department students who took Reading IV class, participated in this project. There were three cycles with three different critical reading strategies were applied. Meanwhile, the authentic materials were taken from newspaper and internet articles. The result revealed that the use of critical reading strategies along with the use of authentic materials has improved students’ critical reading skills as seen from the improvement of each cycle - the students critical reading skill was 54% (fair) in the cycle 1 improved to 68% (average) in cycle 2), and 82% (good) in cycle 3.. In addition, based on the critical reading skill criteria, the students’ critical reading skill has improved from 40% (nearly meet) to 80% (exceed). Meanwhile, from the students’ perception questionnaire, it was shown that 63% students agreed the critical reading activity using authentic text could improve critical thinking and 58% students agreed that doing critical reading activity could improve reading comprehension. The result had the implication that the use of authentic texts could improve students’ critical reading skills if it was taught by performing not lecturing them. Selectively choosing various strategies and materials can trigger students’ activeness in responding to a text, that eventually shape their critical reading skills.